2022
DOI: 10.5772/intechopen.99430
|View full text |Cite
|
Sign up to set email alerts
|

Incorporation of Novel Elements in Bioactive Glass Compositions to Enhance Implant Performance

Abstract: Increasing popularities of bioactive-glasses and their potential medical applications have led to countless studies into improving their material characteristics and overall performance. Some scientists hope to create new bioactive-glass compositions, while others seek to merely modify existing ones such as the novel 45S5 bioactive-glass composition; created by Dr. Larry Hench. These modifications aim to address potential complications that may arise at a site following implantation such as bacterial infection… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 36 publications
0
3
0
Order By: Relevance
“…Similarly, it has been demonstrated that Cu-doped BGs and scaffolds promote endothelial cell proliferation and increase mesenchymal stem cell (MSC) differentiation levels. 118,119 To improve bone healing and anti-tumor therapy via the osteogenic properties of Cu, Libin et al 120 recently doped BBG nanoparticles with Cu. According to an in vitro study, the nanoparticle increased endothelial cell angiogenesis as well as the differentiation potential of bone marrow stromal cells (BMSCs).…”
Section: Doping Ions' Role In Regulating Bbg Degradation Rate and Ost...mentioning
confidence: 99%
“…Similarly, it has been demonstrated that Cu-doped BGs and scaffolds promote endothelial cell proliferation and increase mesenchymal stem cell (MSC) differentiation levels. 118,119 To improve bone healing and anti-tumor therapy via the osteogenic properties of Cu, Libin et al 120 recently doped BBG nanoparticles with Cu. According to an in vitro study, the nanoparticle increased endothelial cell angiogenesis as well as the differentiation potential of bone marrow stromal cells (BMSCs).…”
Section: Doping Ions' Role In Regulating Bbg Degradation Rate and Ost...mentioning
confidence: 99%
“…Moreover, the concentration of the dopant should be determined, because the low dopant concentrations sometimes may not produce the desired properties, and on the contrary, high dopant concentrations may have cytotoxic and carcinogenic effects [ 46 ].…”
Section: Bioactive Glassesmentioning
confidence: 99%
“…Its remarkable bioactivity, particularly in the context of coating metal implants, exceeds that of conventional biomaterials. The crucial factor to its effectiveness lies in the formation of a strong, carbonated hydroxyapatite layer that mimics the structure of the host bone, ensuring an effective chemical bond and thereby emphasizing the stability of the implant [13,[17][18][19][20]. Moreover, bioglass exhibits inherent osteoinductive and osteogenic properties, stimulating the recruitment and differentiation of human primary osteoblasts, thereby enhancing their proliferation [16,21,22].…”
Section: Introductionmentioning
confidence: 99%